2022
DOI: 10.1051/0004-6361/202142387
|View full text |Cite
|
Sign up to set email alerts
|

Modelling simple stellar populations in the near-ultraviolet to near-infrared with the X-shooter Spectral Library (XSL)

Abstract: We present simple stellar population models based on the empirical X-shooter Spectral Library (XSL) from near-ultraviolet (NUV) to near-infrared (NIR) wavelengths. The unmatched characteristics of the relatively high resolution and extended wavelength coverage (350–2480 nm, R ∼ 10 000) of the XSL population models bring us closer to bridging optical and NIR studies of intermediate-age and old stellar populations. It is now common to find good agreement between observed and predicted NUV and optical properties … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 128 publications
(189 reference statements)
0
10
0
Order By: Relevance
“…The provided XSL abundance catalogue, which has an excellent parameter coverage for intermediate and old stellar populations and a wide metallicity range, follows the abundance pattern of the Galaxy. Therefore, stellar population models based on the XSL will provide predictions that follow the same pattern (Verro et al 2022a). However, the abundance ratios determined here are required for building up models with varying Mg and Ca abundances.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The provided XSL abundance catalogue, which has an excellent parameter coverage for intermediate and old stellar populations and a wide metallicity range, follows the abundance pattern of the Galaxy. Therefore, stellar population models based on the XSL will provide predictions that follow the same pattern (Verro et al 2022a). However, the abundance ratios determined here are required for building up models with varying Mg and Ca abundances.…”
Section: Discussionmentioning
confidence: 95%
“…The XSL can be considered as a reference stellar library in the optical and NIR. Simple stellar population models based on the XSL were recently presented by Verro et al (2022a).…”
Section: Introductionmentioning
confidence: 99%
“…They contain stellar spectra of a number of pre-selected stars in different wavelength regimes (UV, visible, NIR), a variety of spectral resolutions, and with varied attention to flux calibration. Examples include a library of stellar spectra by Jacoby et al (1984), XSHOOTER (Verro et al 2022a), MILES (Sánchez-Blázquez et al 2006), Indo-US (Valdes et al 2004), IRTF (Cesetti et al 2013), ELODIE (Soubiran et al 1998;Prugniel et al 2007), Lick (Worthey et al 1994(Worthey et al , 2014, and UVES-POP (Bagnulo et al 2003) libraries. Such libraries are often incorporated into stellar population synthesis models.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral resolution and wavelength coverage vary among the various existing libraries (c.f. Table 1 of Verro et al 2022a), but none of them extend shortward of 300 nm into the ultraviolet (UV) regime except those of and Fanelli et al (1990), who present 172 and 218 stellar spectra, respectively, observed by the International Ultraviolet Explorer (IUE). An important motivation for the present HST-based library is to relieve the relative scarcity of spectral data in the UV.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the MILES library (Sánchez-Blázquez et al 2006) was used to compute simple stellar population (SSP) spectral energy distributions (SEDs) in the optical wavelength range with comprehensive metallicity coverage (Vazdekis et al 2010;Falcón-Barroso et al 2011). There are many other examples, such as Bruzual & Charlot (2003), Verro et al (2022b), Le Borgne et al (2004), Vazdekis et al (2012), and Worthey et al (2022b). On a star-by-star basis, libraries can be used to infer stellar parameters like T eff , g log , and [Fe/H] (e.g., Wu et al 2011).…”
Section: Introductionmentioning
confidence: 99%